L’adaptation des femmes professionelles à la carrière, à la maternité et aux responsabilités familiales - Cyr, Mireille; David, Hélène (Canadian Journal of Counselling and Psychotherapy, 2011)
A study dealing with the dual problem of raising children and pursuing an academic career was conducted with 181 female professors and university researchers. The data confirmed the existence of a conflict between these two roles and notably that these women experience serious difficulties in availing themselves of their right to maternity leave and that they feel obligated to take on more work both at home and at the university. Nevertheless, the majority of respondents say that they were satisfied or very satisfied by the way they have accommodated their family life to their professional responsibilities although they recognize that they had to make sacrifices with regard to their social and cultural life. Finally, the number of women having no children led us to believe that many professors have put the emphasis on their professional rather than family life. Research and intervention implications are discussed.